Does Aberrant Membrane Transport Contribute to Poor Outcome in Adult Acute Myeloid Leukemia? - Alexandre eChigaev (Frontiers Media S.A., 2015)
Acute myeloid leukemia (AML) in adults is a highly heterogeneous disease. Gene expression profiling performed using unsupervised algorithms can be used to distinguish specific groups of patients within a large patient cohort. The identified gene expression signatures can offer insights into underlying physiological mechanisms of disease pathogenesis. Here, the analysis of several related gene expression clusters associated with poor outcome, worst overall survival and highest rates of resistant disease and obtained from the patients at the time of diagnosis or from previously untreated individuals is presented. Surprisingly, these gene clusters appear to be enriched for genes corresponding to proteins involved in transport across membranes (transporters, carriers and channels). Several ideas describing the possible relationship of membrane transport activity and leukemic cell biology, including the Warburg effect, the specific role of chloride ion transport, direct import of metabolic energy through uptake of creatine phosphate, and modification of the bone marrow niche microenvironment are discussed.